2018
DOI: 10.1111/coep.12414
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Marijuana Dispensary Openings on Housing Prices

Abstract: We evaluate the effect of medical and recreational dispensary openings on housing prices in Denver, Colorado. Using an event study approach, we find that the introduction of a new dispensary within a half‐mile radius of a new home increases home prices by approximately 7.7% on average. The effect diminishes for homes further from new dispensaries but is consistent over time. Our results provide important and timely empirical evidence on the socioeconomic impacts of marijuana legalization. (JEL R32, R38, R5)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…Table 2, column (3) adds census tract by year fixed effects. Under this specification, the estimated effect of a dispensary is slightly positive, consistent with the prior research (Conklin, Diop andLi 2017, Burkhardt andFlyr 2018). However, this specification does not account for the possibility that dispensary location is endogenous to differential price trends within tracts.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Table 2, column (3) adds census tract by year fixed effects. Under this specification, the estimated effect of a dispensary is slightly positive, consistent with the prior research (Conklin, Diop andLi 2017, Burkhardt andFlyr 2018). However, this specification does not account for the possibility that dispensary location is endogenous to differential price trends within tracts.…”
Section: Resultssupporting
confidence: 73%
“…However, Conklin, Diop and Li (2017) remained agnostic regarding the true underlying causal mechanisms. Burkhardt and Flyr (2018) also examined the Denver market and followed a similar methodology to Conklin, Diop and Li (2017), but estimated the average effect of a local dispensary generally, rather than estimating the effect of conversions from medical providers to recreational dispensaries. The study found that a home within a half-mile of a dispensary sold at an 8% premium, confirming the positive effect identified in Conklin, Diop and Li (2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retailers may choose to locate in a specific place for a variety of reasons, like anticipating greater demand for marijuana, greater visibility to the public, cheaper property, or lower chances of being required to move by local laws and regulations. Additionally, individuals may choose to move toward or away from retailers, due to an appreciation/aversion of marijuana, concerns of effects on family members, or perceived effects on property values (Burkhardt & Flyr, 2018; Conklin et al, 2017). We examine the effect of travel time on various demographic characteristics to see if stores tend to locate near certain groups of people or if these groups tend to move in response to new stores.…”
Section: Robustness Checksmentioning
confidence: 99%
“… See, for example, Burkhardt and Flyr (2018) and Swensen (2015) for studies that address concerns of endogenous marijuana retail and substance abuse treatment clinic locations, respectively. …”
mentioning
confidence: 99%